2013
DOI: 10.1038/npp.2013.273
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Tobacco Exposure and Brain Morphology: A Prospective Study in Young Children

Abstract: It is well known that smoking during pregnancy can affect offspring health. Prenatal tobacco exposure has been associated with negative behavioral and cognitive outcomes in childhood, adolescence, and young adulthood. These associations between prenatal tobacco exposure and psychopathology in offspring could possibly be explained by the influence of prenatal tobacco exposure on brain development. In this prospective study, we investigated the association between prenatal tobacco exposure, behavioral and emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 50 publications
7
76
1
2
Order By: Relevance
“…Both steps of quality control had to be passed successfully in order for data to be included in the analyses. 29 Neuroimaging measures of interest were cortical thickness and gyrification. We calculated cortical thickness as the closest distance from the grey/white matter boundary to the grey matter/cerbrospinal fluid (CSF) boundary at each vertex on the tessellated surface.…”
Section: Cortical Morphologymentioning
confidence: 99%
“…Both steps of quality control had to be passed successfully in order for data to be included in the analyses. 29 Neuroimaging measures of interest were cortical thickness and gyrification. We calculated cortical thickness as the closest distance from the grey/white matter boundary to the grey matter/cerbrospinal fluid (CSF) boundary at each vertex on the tessellated surface.…”
Section: Cortical Morphologymentioning
confidence: 99%
“…113 In two recent, well controlled studies with large populations (n > 100), alterations in cortical morphology in children with prenatal exposure to tobacco and/or marijuana were shown. 114,115 Polysubstance exposure is common in populations of prenatally drug-exposed children. Results from a volumetric MRI study of children with prenatal exposure to alcohol, tobacco, cocaine and marijuana suggested that these substances may act cumulatively during gestation to exert long lasting effects on brain volumes.…”
Section: Mri Studies Of Prenatally Drug-exposed Childrenmentioning
confidence: 99%
“…Volumetric measures from FreeSurfer have been validated against manual segmentation 129 and the method has been widely used in previous pediatric studies. 114,139,140 Head motion during MRI acquisition can affect the automated volumetric estimates. 141 It is however, unlikely that head motion artifacts could explain the observed group differences in volumetric brain measures, as there was no significant difference between exposed and unexposed children in the quality score given to the MRI scans based on the grade of movement artifacts.…”
Section: Mri Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal tobacco exposure was associated with reductions in fetal head growth, reduced volume of the frontal lobes and cerebellum, and smaller width of the lateral ventricles [62,63]. During childhood, prenatal tobacco exposure is associated with additional changes in brain structure including smaller total brain volume and smaller cortical gray matter volume [36,64], cortical thinning in superior frontal and parietal cortices [64] and reduced gray matter volume in subcortical regions including the amygdala, thalamus, and pallidum [59,65]. Increased volume in the frontal cortex with corresponding decreases in the anterior cingulate cortex was also observed [66].…”
Section: Maternal and Environmental Variablesmentioning
confidence: 99%